ANALYSIS OF THE ABILITY OF READING CLASS 1 BASIC SCHOOL STUDENTS IN STATE BASIC SCHOOL 009 KEPAU JAYA SIAK HULU KAMPAR DISTRICT - Muhammad Halim; Neni Hermita; Otang Kurniaman (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2020)
The background of this research is the problem of reading ability of grade 1 elementary school students in 009 Kepau Jaya Public Elementary School, Siak Hulu Subdistrict, Kampar Regency, as seen by students who have difficulty recognizing letters, even though the teacher often repeats the letters in front of the class, saying words, and matching pictures with writing when the teacher uses the task of matching images with children's writing tends to be less able to do it. This study aims to analyze the reading ability of grade 1 elementary school students at 009 Kepau Jaya Public Elementary School. The population and sample in this study were all first-grade students of 009 Public Elementary School Siak Hulu, Siak Hulu Subdistrict, amounting to 30 students. The method used in this research is quantitative descriptive to analyze the reading ability of grade 1 elementary school students at 009 Kepau Jaya Public Elementary School, Siak Hulu District, Kampar District. The data collection technique used was the observation of grade 1 students and analyzed to find out the results of descriptive statistics that illustrated the level of ability to educate elementary school students in grade 1. Based on the results of the study it was found that the ability to read first-grade students of 009 Kepau Jaya Public Elementary School in Siak Hulu District was a low category. This can be seen in the category of scores obtained by students where 18 or 60% of students are in the low initial reading ability, while the remaining 12 or 40% of students are in moderate reading ability. This is influenced by physiological factors, intellectual factors, environmental factors, and psychological factors.